Dysferlinopathy misdiagnosed with juvenile polymyositis in the pre-symptomatic stage of hyperCKemia: a case report and literature review - Cecilia Contreras-Cubas; Francisco Barajas-Olmos; Maria Inés Frayre-Martínez; Georgina Siordia-Reyes; Claudia C. Guízar-Sánchez; Humberto García-Ortiz; Lorena Orozco; Vicente Baca (BMC, 2022)
Abstract Background Dysferlinopathy encompasses a group of rare muscular dystrophies caused by recessive mutations in the DYSF gene. The phenotype ranges from asymptomatic elevated serum creatine kinase (hyperCKemia) to selective and progressive involvement of the proximal and/or distal muscles of the limbs. Bohan and Peter criteria are the most widely used for the diagnosis of polymyositis, but they have limitations and can misclassify muscular dystrophies with inflammation as polymyositis. Most dysferlinopathy patients have muscle biopsies with inflammation and thus are vulnerable to misdiagnosis with polymyositis and inappropriate treatment with steroids and immunosuppressors. Case presentation We describe a 14 years-old male patient who was referred for assessment of asymptomatic hyperCKemia (26,372 IU/L). An X-linked dystrophinopathy initially was ruled out by direct genetic testing. Juvenile polymyositis was considered based on muscle biopsy, creatine kinase levels, and electromyography changes. Corticosteroid treatment triggered proximal lower limb muscular weakness, and no full muscular strength recovery was observed after corticosteroid withdrawal. Based on these observations, a limb-girdle muscular dystrophy (LGMD) was suspected, and LGMDR2 was confirmed by whole exome sequencing. Conclusion We report a dysferlinopathy patient who was misdiagnosed with juvenile polymyositis and explore in a literature review how common such misdiagnoses are. With diagnosis based only on routine clinicopathological examinations, distinguishing an inflammatory myopathy from dysferlinopathy is quite difficult. We suggest that before establishing a diagnosis of "definite" or "probable" juvenile polymyositis, according to Bohan and Peter or current ACR/EULAR criteria, a muscular dystrophy must first be ruled out.